Resistance training instuction trunk - Aarberg, Everet; Fink, Doug; Human Kinetics (Firm) (Illnois : Human Kinetic, 2001)
Focuses on strengthening and developing the trunk and core muscles. The core muscles, or'inner unit', work interdependently with the outer abdominal and oblique musculature to stabilize the spine and produce a variety of movements
Title from title screen
Scripwriter, R. Chris Johns, Everett Aaberg
Keywords: Weight training; Exercise; Personal trainers